Comparison of Macrophage Migration-Inhibitory-Factor (MIF) Serum Level between 28 - 36 Weeks of Pregnancy and Delivery - Novy Riyanti (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objective: To analyze the differences in Macrophage Migration Inhibitory Factor (MIF) serum level between 28 - 36 weeks of pregnancy and delivery, and determine the serum level of Macrophage MIF as a risk factor for preterm labor. Methods: The design of our study was cross sectional of 72 subjects who met the inclusion- and exclusion-criteria that came to Dr. Hasan Sadikin Hospital, Bandung and six satelite hospitals (in July - August 2011). Macrophage Migration Inhibitory Factor (MIF) level was measured with ELISA. Comparison of mean serum levels of MIF between 28 - 36 weeks of pregnancy and delivery was analyzed using the Mann Whitney test. MIF level, which is a risk factor for preterm delivery, was calculate with a prevalence ratio (PR) based on ROC curve. Results: Characteristics test in both groups showed homogeneous and comparable data. The mean levels of Macrophage Migration Inhibitory Factor (MIF) in 28 - 36 weeks of delivery was higher (54.433 ng/ml) compared with 28 - 36 weeks of gestation (31.765 ng/ml) with p â‰¤ 0.001. MIF levels > 37.684 ng/ml had a risk for preterm labor incidence 3.35 times greater than that of â‰¤ 37.684 ng/ml. Conclusion: Serum levels of Macrophage Migration Inhibitory Factor (MIF) at delivery was higher than that of at 28 - 36 weeks pregnancy. MIF levels > 37.684 is a risk factor for preterm labor. [Indones J Obstet Gynecol 2011; 35-3: 115-8] Keywords: Macrophage Migration-Inhibitory-Factor (MIF), preterm labor